Genome-Wide Association Analyses Track Genomic Regions for Resistance to Ascochyta rabiei in Australian Chickpea Breeding Germplasm - Raman, Rosy; Warren, Annie; Krysinska-Kaczmarek, Marzena; Rohan, Maheswaran; Sharma, Niharika; Dron, Nicole; Davidson, Jenny; Moore, Kevin; Hobson, Kristy (Frontiers in Plant Science, 2022)
Ascochyta blight (AB), caused by a necrotrophic fungus, Ascochyta rabiei (syn. Phoma rabiei) has the potential to destroy the chickpea industry worldwide, due to limited sources of genetic resistance in the cultivated gene pool, high evolutionary potential of the pathogen and challenges with integrated disease management. Therefore, the deployment of stable genetic resistance in new cultivars could provide an effective disease control strategy. To investigate the genetic basis of AB resistance, genotyping−by−sequencing based DArTseq−SNP marker data along with phenotypic data of 251 advanced breeding lines and chickpea cultivars were used to perform genome−wide association (GWAS) analysis. Host resistance was evaluated at seven weeks after sowing using two highly aggressive single spore isolates (F17191−1 and TR9571) of A. rabiei. GWAS analyses based on single−locus and multi−locus mixed models and haplotyping trend regression identified twenty−six genomic regions on Ca1, Ca4, and Ca6 that showed significant association with resistance to AB. Two haplotype blocks (HB) on chromosome Ca1; HB5 (992178−1108145 bp), and HB8 (1886221−1976301 bp) were associated with resistance against both isolates. Nine HB on the chromosome, Ca4, spanning a large genomic region (14.9 Mbp to 56.6 Mbp) were also associated with resistance, confirming the role of this chromosome in providing resistance to AB. Furthermore, trait−marker associations in two F2:3 derived populations for resistance to TR9571 isolate at the seedling stage under glasshouse conditions were also validated. Eighty−nine significantly associated SNPs were located within candidate genes, including genes encoding for serine/threonine−protein kinase, Myb protein, quinone oxidoreductase, and calmodulin−binding protein all of which are implicated in disease resistance. Taken together, this study identifies valuable sources of genetic resistance, SNP markers and candidate genes underlying genomic regions associated with AB resistance which may enable chickpea breeding programs to make genetic gains via marker−assisted/genomic selection strategies.